Determinants of Antepartum Human Immunodeficiency Virus Testing in a Non-Medicaid Obstetric Population. Issue 5 (1998) - Cardonick, E.; Daly, S.; Dooley, M.; Elles, K.; Silverman, N. S.
Abstract : Objective: To determine voluntary human immunodeficiency virus (HIV) testing rates and factors influencing testing in a private obstetric practice. Methods: Antepartum patients were offered HIV testing after completing a self-assessment questionnaire. Perceived risks and demographics were correlated with testing rates. Results: Overall, 348/600 (58%) women consented to HIV testing. In a univariate analysis, patients with "any" perceived risk(s) were more likely to be tested. Single women and those with an at-risk partner(s) or a history of sexually transmitted disease (STD) were more likely to desire testing. These factors remained independently associated with voluntary testing in a multivariate regression model. No patients tested positive for HIV. Conclusions: In our private obstetric practice, 26% of women perceived themselves at risk for HIV infection, and testing rates depended on the various risks identified. A history of STDs or an at-risk sexual partner were stronger predictors of voluntary testing than was marital status. Focused HIV counseling among pregnant women at relatively low risk for infection may be possible.